Physical Fitness Training Strategies to Improve Operational Readiness of Indonesian Army Soldiers in High-Risk Areas of Papua - Thega, Rogery (UNIB Press, 2026)
Physical fitness training plays a strategic role in preparing Indonesian Army (TNI AD) soldiers for Security Operations in Conflict-Prone Areas (Pamrahwan) in Papua, which are characterized by rugged terrain, extreme weather, and dynamic threat conditions. This study aims to analyze the physical fitness condition of Pamrahwan soldiers, identify constraints in physical fitness training within operational areas, and formulate effective training strategies to enhance operational readiness. A qualitative approach was employed through in-depth interviews with soldiers, physical fitness instructors (Bajas/Pajas), and command elements. Data were analyzed using NVivo through coding, categorization, and thematic analysis. The findings indicate that soldiers’ physical fitness levels are generally functional and adaptive; however, training has not been fully implemented through structured, periodization-based programs. Key constraints include environmental conditions, limited facilities, security threats, and intensive operational schedules. The study concludes that physical fitness training must be conducted through a systematic, adaptive, and doctrinally aligned approach to ensure optimal operational readiness.